Legal Certainty Regarding Buyback Guarantees in Banking Agreements - Citra, Helfira; Wahyuni, Sry; Fauzi, Engrina; Adbaida, Adbaida (Jurnal Ilmiah Ekotrans & Erudisi, 2024)
Indonesia is in the development stage in all areas, including facilities and infrastructure in the form of construction and rehabilitation of roads, bridges, public housing, office buildings and public facilities. Meanwhile, development in the spiritual sector includes government development in the fields of education, religion, social, culture and politics. The government always strives for development to be carried out in an optimal manner, whether with short-term, medium-term or long-term development.  The desire for a residence is a person's (personal) achievement where it is a personal priority for each individual, some people may consider that the quality of a human's life is incomplete if they do not have a residence or private residence. In this way, a residence or house is not just a place to shelter, but everyone wants their residence/home to have elements of comfort and security, various public and social facilities and adequate facilities and infrastructure. What is an obstacle for every individual here is the limitation in getting ideal housing? Thus, the discussion regarding housing/settlement is of concern to both parties, not just to the dominance of the individual. The parties involved in this include consumers (debtors), developers (developers) and the bank as creditor.